2001
DOI: 10.1073/pnas.201413498
|View full text |Cite
|
Sign up to set email alerts
|

LEAFY COTYLEDON2encodes a B3 domain transcription factor that induces embryo development

Abstract: The Arabidopsis LEAFY COTYLEDON2 (LEC2) gene is a central embryonic regulator that serves critical roles both early and late during embryo development. LEC2 is required for the maintenance of suspensor morphology, specification of cotyledon identity, progression through the maturation phase, and suppression of premature germination. We cloned the LEC2 gene on the basis of its chromosomal position and showed that the predicted polypeptide contains a B3 domain, a DNA-binding motif unique to plants that is charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
686
2
7

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 687 publications
(739 citation statements)
references
References 46 publications
21
686
2
7
Order By: Relevance
“…Here we show that ectopic BBM expression in combination with cytokinin is suYcient to induce somatic embryogenesis in tobacco seedlings, suggesting that BBM acts by bypassing the need for one or more of these plant growth regulators. Spontaneous somatic embryogenesis has been observed in a number of Arabidopsis mutants, including the gain-of-function LEAFY COT-YLEDON1 (LEC1) and LEC2 mutants (Lotan et al 1998;Stone et al 2001) and the pickle (pkl) loss-offunction mutant (Ogas et al 1997). Both LEC proteins and PKL appear to function in the context of hormone signalling pathways to activate spontaneous somatic embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we show that ectopic BBM expression in combination with cytokinin is suYcient to induce somatic embryogenesis in tobacco seedlings, suggesting that BBM acts by bypassing the need for one or more of these plant growth regulators. Spontaneous somatic embryogenesis has been observed in a number of Arabidopsis mutants, including the gain-of-function LEAFY COT-YLEDON1 (LEC1) and LEC2 mutants (Lotan et al 1998;Stone et al 2001) and the pickle (pkl) loss-offunction mutant (Ogas et al 1997). Both LEC proteins and PKL appear to function in the context of hormone signalling pathways to activate spontaneous somatic embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…(Kakimoto 1996;Lotan et al 1998;Hewelt et al 2000;Banno et al 2001;Stone et al 2001;Boutilier et al 2002;Zuo et al 2002). Most of these genes have been identiWed in Arabidopsis [Arabidopsis thaliana (Heyhn) L.] and many of them encode transcription factors or proteins involved in signal transduction.…”
Section: Introductionmentioning
confidence: 99%
“…All four abi3, lec1, lec2 and fus3 mutants are severely affected in seed maturation and share some common phenotypes, such as decreased dormancy at maturation (Raz et al, 2001) and reduced expression of seed storage proteins (Gutierrez et al, 2007). However, they also show specific phenotypes, such as the absence of chlorophyll degradation in the dry seed (abi3), a reduced sensitivity to ABA (abi3 and, to a lesser extent, lec1), the accumulation of anthocyanins (fus3, lec1, and, to a lesser extent, lec2), an intolerance to desiccation (abi3, fus3, and lec1), or defects in cotyledon identity (lec1, fus3, and lec2) (Bäumlein et al, 1994; Keith et al, 1994;Meinke et al, 1994;Parcy et al, 1994;Parcy & Giraudat, 1997;Luerssen et al, 1998;Vicient et al, 2000;Raz et al, 2001;Stone et al, 2001; Kroj et al, 2003). It was recently shown that several of the fus3 phenotypes are due to pleiotropic effects caused by truncated gene products of the mutant alleles.…”
Section: Genes and Factors Affected In Seed Dormancy/germinationmentioning
confidence: 99%
“…ABA-INSENSITIVE3 (ABI3), FUSCA3 (FUS3) and LEAFY COTYLEDON (LEC1 and LEC2) are four key regulators that play prominent roles in controlling mid-and late seed development (Meinke et al, 1994;Raz et al, 2001). ABI3, FUS3 and LEC2 encode related plant-specific transcription factors containing the conserved B3 DNA binding domain (Giraudat et al, 1992;Luerssen et al, 1998;Stone et al, 2001), whereas LEC1 encodes a HAP3 subunit of the CCAAT binding transcription factor (CBF, also known as NF-Y (Lotan et al, 1998)). All four abi3, lec1, lec2 and fus3 mutants are severely affected in seed maturation and share some common phenotypes, such as decreased dormancy at maturation (Raz et al, 2001) and reduced expression of seed storage proteins (Gutierrez et al, 2007).…”
Section: Genes and Factors Affected In Seed Dormancy/germinationmentioning
confidence: 99%
“…Ectopic expression of the seed-specific CCAAT-box binding factor LEAFY COTYLEDON1 (LEC1) and the B3 domain transcription factor, LEC2 also promote somatic embryo formation on seedlings (Lotan et al 1998;Stone et al 2001). Loss-of-function lec1 and lec2 mutants are impaired in embryo identity and maturation, indicating their broad role as regulators of embryo development (reviewed in Harada 2001).…”
Section: Introductionmentioning
confidence: 99%